DISABILITY RIGHTS IN THE SUB-REGIONAL ECONOMIC COMMUNITIES DURING 2013 (African Disability Rights Yearbook, 2021)
Although the core purpose of the sub-regional economic communities is the pursuit of economic integration, certain key opportunities have been identified for the inclusion of human rights, and particularly disability rights, in the purview of these Communities. This subsection reports on recent events relating to disability rights in one of these, namely the East Africa Community (EAC); there have been no notable developments in the Southern African Development Community (SADC) and the Economic Community of Western African States (ECOWAS) during the period under review.